Correlations between CD4+FoxP3+ Treg and expression of FoxM1 and Ki‐67 in gastric cancer patients. Issue 2 (19th January 2020) - Ma, Kai; Li, Xiaoxiao; Lv, Jing; Liu, Zimin; Zhang, Lijian; Cong, Hui; Wang, Huiyun; Shen, Fangzhen; Yue, Lu
Abstract: Aims: In this study, we intended to analyze the clinical significance of CD4 + FoxP3 + Tregs in gastric cancer patients and investigate the relationship between the proportion of CD4 + FoxP3 + Tregs in the peripheral blood and the expression of FoxM1 and Ki‐67 in gastric cancer tissues. Methods: Flow cytometry was used to measure the CD4 + FoxP3 + Tregs level in peripheral blood from 70 gastric cancer patients one day before gastrectomy and D2 lymph node dissection. Immunohistochemistry staining was used to detect the expression of FoxM1 and Ki‐67 in gastric cancer tissues. Data on clinico‐pathological features and correlation between Tregs and the expression of FoxM1 and Ki‐67 were then analyzed. Results: The average proportion of CD4 + FoxP3 + Tregs in gastric cancer patients' peripheral blood before surgery was 10.12 ± 2.85%, which was significantly higher in patients with late AJCC stage ( P = 0.029) or lymph node metastasis ( P = 0.003) compared to patients at earlier AJCC stage or without lymph node metastasis. The levels of CD4 + FoxP3 + Treg cells was positively correlated with the protein expression of FoxM1 ( P = 0.003) and Ki‐67 ( P = 0.001), respectively. Conclusion: These results suggest the level of CD4 + FoxP3 + Treg cells in peripheral blood has clinical significance in gastric cancer patients. The overexpression of FoxM1 and Ki‐67 may relate to immunosuppression in gastric cancer.